CTNI-65. COMBINED RITUXIMAB, METHOTREXATE, PROCARBAZINE, VINCRISTINE, AND CYTARABINE (R-MPV-A) TREATMENT FOR PATIENTS WITH RELAPSED PRIMARY CNS LYMPHOMA - Nagane, Motoo (Neuro Oncol, 2020)
BACKGROUNDS: Standard of care for patients with primary CNS lymphoma (PCNSL) has been high-dose methotrexate (HD-MTX)-based multiagent immunochemotherapy including an induction R-MPV with consolidation whole-brain radiotherapy (WBRT) and HD-cytarabine to achieve complete remission, however, the optimal treatment for relapsed/refractory (r/r) PCNSL has not been established yet, besides the recent approval of a BTK inhibitor, tirabrutinib, in Japan. We evaluated retrospectively efficacy of R-MPV-A for r/rPCNSL. PATIENTS: Histologically proven PCNSL patients treated at relapse in our institution from April 2000 to November 2019 were analyzed. Outcomes were compared between those treated with RMPVA or other regimens. RESULTS: Among 148 PCNSL patients identified, 73 had at least one relapse, of whom 47 received salvage chemotherapy including 23 treated with RMPVA either at the first relapse (11) or at the second or later relapse (12). Median age/KPS of this salvage RMPVA group were 71 (42–87)/80 (40–100). Nine patients were pretreated with the first-line RMPVA. HD-cytarabine was given to 13 patients. Median number of RMPV cycles was 8 (1–4 cycles: 10; 8 cycles 13). CR/CRu were achieved in 19 (83%), response rate was 87%, while there were two PDs (9%). After median follow-up of 21.9 months, the median PFS after salvage RMPVA was 13.0 m (95%CI: 9.1–16.9), 1-year overall survival (OS) was 82%, median OS was 70.0 m (95%CI: 12.9–127.1), which were longer than those in 24 patients with salvage treatment other than RMPVA (mPFS 4.4 m, P=0.054; mOS 13.6 m, P=0.009). Among patients with salvage RMPVA, HD-cytarabine was associated with better PFS (P=0.066), and complete responses were significantly correlated with longer OS. Treatment was generally well-tolerated but there was one treatment-related death. CONCLUSIONS: Salvage RMPVA at relapses was active and associated with longer survival compared with other regimens, necessitating further development of salvage regimens incorporating tirabrutinib in the future studies.